Auditory Brainstem Implant Array Position Varies Widely Among Adult and Pediatric Patients and Is Associated With Perception - Barber, Samuel R; Kozin, Elliott D; Remenschneider, Aaron K; Puram, Sidharth V; Smith, Max; Herrmann, Barbara S; Cunnane, Mary E; Brown, M Christian; Lee, Daniel J (Ear and hearing, 2017)
The auditory brainstem implant (ABI) provides sound awareness to patients who are ineligible for cochlear implantation. Auditory performance varies widely among similar ABI cohorts. We hypothesize that differences in electrode array position contribute to this variance. Herein, we classify ABI array position based on postoperative imaging and investigate the relationship between position and perception. Retrospective review of pediatric and adult ABI users with postoperative computed tomography. To standardize views across subjects, true axial reformatted series of scans were created using the McRae line. Using multiplanar reconstructions, basion and electrode array tip coordinates and array angles from vertical were measured. From a lateral view, array angles (V) were classified into types I to IV, and from posterior view, array angles (T) were classified into types A to D. Array position was further categorized by measuring distance vertical from basion (D1) and lateral from midline (D2). Differences between array classifications were compared with audiometric thresholds, number of active electrodes, and pitch ranking. Pediatric (n = 4, 2 with revisions) and adult (n = 7) ABI subjects were included in this study. Subjects had a wide variety of ABI array angles, but most were aimed superiorly and posteriorly (type II, n = 7) from lateral view and upright or medially tilted from posterior view (type A, n = 6). Mean pediatric distances were 8 to 42% smaller than adults for D1 and D2. In subjects with perceptual data, electrical thresholds and the number of active electrodes differed among classification types. In this first study to classify ABI electrode array orientation, array position varied widely. This variability may explain differences in auditory performance.